ANALISIS PELATIHAN KOMUNIKASI LINTAS BUDAYA PADA PERUSAHAAN MULTINASIONAL (Studi Kasus PT Kawasan Industri Nusantara KEK Sei Mangkei) - wida yustika (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2025)
International business is a business activity carried out between one country and another. International business activities can be carried out in various forms of Foreign Direct Investment, licensing, franchising, and multinational corporation (MNC). According to Rugman, a multinational company is a company that produces abroad in addition to the parent country and operates across national borders. The development of multinational companies in Indonesia is currently very rapid supported by Indonesia's growing economic conditions. The increasing number of multinational companies in Indonesia also goes hand in hand with the increasing need to hire more workers from various countries that allow them to communicate with foreign workers stationed in Indonesia. Interaction that occurs beyond the boundaries of language and cultural differences, demanding the ability of each party to be able to understand the differences that exist is referred to as intercultural communication. The purpose of this study is to analyze how cross-cultural communication training in multinational companies in the Nusantara Industrial Zone SEZ Sei Mangkei. This research uses a qualitative method that produces descriptive data in the form of written, spoken words from people and observed behavior. With data collection techniques, namely library research, questionnaires and observation. The results showed that cross-cultural communication training at the multinational company Nusantara Industrial Estate SEZ Sei Mangkei was motivated by the existence of cross-cultural communication barriers with foreign investors, namely language differences that can lead to misunderstandings and failure of business agreements. To ensure that its employees use the English language skills acquired from the training program, the company implements daily work in speaking English.